Kurangnya Keterampilan Berpikir Kritis Pada Pelajaran IPS di SD Negeri 10 Sapuli Kota Makassar - Latang; Amir Pada (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This Research problem is high order thinking of students still low. Teaching is oriented by the teacher and the teacher is giving less motivation to the student. The Teacher seldom gives the question to student about high order thinking and the students look for the answer. This research aims to describe the implementation and the increasing of student high order thinking in studying social science by using model learning base problem. This research method is action research in class. This method adapt the model from Taggart and Kemmis conducted with two cycles in the class at SD Neg Makassar. The research subject is five class. There are 32 students. This action research conducted in implementation of learning base problem model that it were five stages as: the student instruction in orientation the problems, in organizing student to learn, in helping student, in developing and in presenting, in analyzing and evaluating the problem solving. The indicator of high order thinking which is measured in this research identify the problem, collect the information, look for, solve the problem, and using the good instruction through the good language. Using the good reason to conclude. This result research showed that the high order thinking of student from first cycle is 59% to second cycle 88%. This research conclusion is the implementation of model learning base problem can increase the skill of high order thinking to student in five class to the social science at elementary school.